Maximizing wireless sensor network lifetime through energy-efficient routing - Prashanth Malligere Vishweshwaraiah; Prema Nisana Siddegowda; Shivashankar Rudraswamy (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Wireless sensor networks (WSNs) are an emerging technology that has the potential to transform the way agricultural farms operate. However, deploying WSNs in agricultural farms presents a unique set of challenges. Limited coverage area, power source availability, data collection and processing, environmental factors, cost, and integration with existing systems are some of the potential problems that need to be addressed when deploying WSNs in agricultural farms. Hence, in this work, we have proposed a method for increasing the lifetime of the sensor network which will help also help to reduce the energy. The proposed method has been evaluated in terms of network lifetime of the sensor nodes, routing and communication overhead. The results have been compared with the existing M-LEACH method and the results show that there is an enhancement of 79.02% for average network lifetime. The results also show that the proposed method reduces the average routing and communication overhead by 49.17% and 38.37% respectively.